Factores asociados a una percepción favorable del trabajo médico en el primer nivel de atención en estudiantes de medicina de 11 países de Latinoamérica 2011-2012 - Pereyra Elías, Reneé (2015)
Objective: To evaluate the differences among Primary Care (PC) labor perceptions of medical students from Latin America according to their country. Methods: Observational, analytic and cross-sectional multicountry study that evaluated 9 561 first and fifth-year medical students from 63 medical schools of 11 Latin American countries through a survey. To evaluate the perceptions on the PC work, a previously validated scale was used. Tertiles of the scores were created in order to compare the different countries. Crude and adjusted prevalence ratios were calculated using simple and multiple Poisson regression. A p-value<0.05 was considered statistically significant. Findings: 52.9% of the subjects were female and the mean age was 20.4±2.9 years. 35.5% were fifth-year students. Statistically significant differences were found between the study subjects’ country, using Peru as reference. Students from Chile, Colombia, Mexico and Paraguay perceived PC work more positively compared with Peruvian students, while those from Ecuador showed less favorable opinions. No differences were found among the perceptions of Bolivian, Salvadoran, Honduran and Venezuelan students when compared to their Peruvian peers. Conclusions: Perceptions of PC among medical students from Latin America vary according to the country. Considering such differences can be of major importance for potential local specific interventions for the improvement of PC in these.